2013
DOI: 10.14260/jemds/533
|View full text |Cite
|
Sign up to set email alerts
|

Acute Undifferentiated Febrile Illness Among Adults – A Hospital Based Observational Study

Abstract: BACKGROUND: Fever is a burning issue in the tropics and the most common cause of morbidity. Quite frequently this fever goes undiagnosed because of many reasons like the lack of diagnostic facilities, insufficient epidemiological data available on causes of fever, and so on. This research study was aimed to find out the etiology and clinical markers of Acute Undifferentiated Febrile Illness [AUFI] among the rural population of Southern India. METHODOLOGY: This prospective, observational study was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
(5 reference statements)
3
10
1
Order By: Relevance
“…Unlike other studies such as Gopalakrishnan et al, (2013), there were no associations with rash and petechiae.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Unlike other studies such as Gopalakrishnan et al, (2013), there were no associations with rash and petechiae.…”
Section: Resultscontrasting
confidence: 95%
“…Typhoid was the commonest cause of AUFI in 28(24.14%) followed by Dengue 12(10.35%). The present study revealed that Typhoid and Dengue were the common causes of AUFI followed by Malaria 6(5.17%), and scrub typhus 2(1.72%), as observed in the previous studies by Thangarasu et al, (2011), Mittal et al, (2015, Singh et al, (2014), Anugrah Chrispal et al, (2010), Rani et al, (2016) and Gopalakrishnan et al, (2013) where the most common causes of AUFI were dengue, Typhoid, Malaria and scrub typhus. In the present study there were 63(54.31%) patients with undiagnosed febrile illness, their clinical outcomes were studied.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Various studies conducted particularly in South India by Chrispal et al, Gopalakrishnan et al, and Kashinkunti et al, have also showed similar results [22,22,23]. In the miscellaneous group of our study, no definite cause was found in 23.7% (64) and was presumed to be of viral origin.…”
Section: Original Research Articlesupporting
confidence: 85%
“…In countries like Thailand, Malaysia and Nepal -dengue, malaria, scrub typhus, leptospirosis and enteric fever have been identified as main causes of AUF. [16][17][18][19][20][21][22] Apart from these four major aetiologies, Abrahamsen et al from South India, in a cohort study, showed that bacterial infections (38%), TB (19%) were also significant common causes of AUF. 19 A study from East India reported that TB (53%), neoplasms ((17%) and Collagen vascular disorders (11%) were also very important causes of fevers.…”
mentioning
confidence: 99%